Sepphoris und die Entwicklung der Synagoge in romiscg-byzantinischer Zeit - Kieweler, H. V. (Journal for semitics, 2003)
The discovery of a well-preserved synagogue in the summer of 1993, confirms the existence of at least one of the 18 synagogues mentioned in the Jerusalem Talmud. It is argued that the combination of education, art, and the restating of beliefs was important in the origin of the synagogue and in the continued strengthening of Judaism. The synagogue at Sepphoris is used to illustrate this during the Byzantine era.